Castle: The complete third season The complete third season - Bowman, Rob; Marlowe, Andrew W.; Fillion, Nathan, 1971-; Katic, Stana; Sullivan, Susan, 1942-; Quinn, Molly C., 1993-; Santiago-Hudson, Ruben, 1956-; Jones, Tamala ([Burbank, Calif.?] : ABC Studios, 2011)
Looking for inspiration, crime novelist Nick Castle becomes a consultant for the New York Police Department and clashes with Detective Kate Beckett.
A deadly affair -- He's dead, she's dead -- Under the gun -- Punked -- Anatomy of a murder -- 3XK -- Almost famous -- Murder most fowl -- Close encounters of the murderous kind -- Last call -- Nikki Heat -- Poof, you're dead -- Knockdown -- Lucky stiff -- The final nail -- Setup -- Countdown -- One life to lose -- Law & murder -- Slice of death -- The dead pool -- To love and die in L.A. -- Pretty dead -- Knockout
originally broadcast on television 2010-2011 ; features: Following a good lead, Castle goes Hollywood, cast and crew interviews, audio commentary, deleted scenes, bloopers.
created by Andrew W. Marlowe ; directed by Rob Bowman ... [et al.] ; written by Andrew W. Marlowe ... [et al.].
Nathan Fillion, Stana Katic, Susan Sullivan, Molly C. Quinn, Ruben Santiago-Hudson, Tamala Jones.
TV rating: TV-14 ; CHV rating: PG.
DVDs, Dolby digital 5.1 surround, widescreen.
In English with optional French or Spanish subtitles ; English SDH.
Keywords: Television series (American); Television programs; Detective and mystery television programs; Detective television programs; Mystery television programs